Hyponatraemia and hypothyroidism: A case report - Giulia Cantoni; Gabriella Nucera; Pietro Marino (Journal of Health and Social Sciences)
In the literature, hypothyroidism-induced hyponatraemia is rare and probably occurs only in severe hypothyroidism characterised by myxoedema. An 82-year-old woman arrived at an emergency department with aphasia and a progressive cognitive impairment associated with walking problems during the last week. Examinations excluded neurological disease. The diagnosis showed a clinically relevant association between hyponatraemia and hypothyroidism disorder characterised by neurological symptoms. In conclusion, this could be one of the few cases, to our knowledge, of non-severe hypothyroidism-induced hyponatraemia.